2015
DOI: 10.1590/0104-1169.0287.2544
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and cognitive-affective depressive symptoms among patients with heart disease: differences by sex and age

Abstract: OBJECTIVE: this study investigated the association of somatic and cognitive-affective symptoms with sex and age, among patients hospitalized with heart disease. METHOD: this study was a secondary analysis of two previous observational studies totaling 531 patients with heart disease, hospitalized from 2005 to 2011 in two public hospitals in Ribeirão Preto, state of São Paulo, Brazil. Somatic and cognitive-affective symptoms were assessed using the subscales of the Beck Depression Inventory - I (BDI-I). RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
2
7
0
6
Order By: Relevance
“…Higher somatic symptoms were also associated with being female and higher depression levels in this study, consistent with previous reports which found females with major depression showed higher rates of somatic symptoms compared to men [61, 62]. A study conducted in Spain, which also used the PHQ-15 to assess for somatic symptoms, found women reported higher total scores than men and were more concerned in 8 out of 15 items of the PHQ-15 [63].…”
Section: Discussionsupporting
confidence: 91%
“…Higher somatic symptoms were also associated with being female and higher depression levels in this study, consistent with previous reports which found females with major depression showed higher rates of somatic symptoms compared to men [61, 62]. A study conducted in Spain, which also used the PHQ-15 to assess for somatic symptoms, found women reported higher total scores than men and were more concerned in 8 out of 15 items of the PHQ-15 [63].…”
Section: Discussionsupporting
confidence: 91%
“…(24) People living with HIV generally present a form of coping through isolation (elusion, selfblame, confrontation, distancing) instead of active coping (problem solving, search for social support, acceptance of responsibility, positive reappraisal). (24) We agree with other researchers that the separate use of the BDI subscales entails implications for clinical practice, (19) as it permits identifying the type and severity of the depression symptoms, which can contribute to the health team's interventions. Depression is a complex disease with multiple symptoms that affect the health and quality of life of the patients in a very particular way.…”
Section: Discussionsupporting
confidence: 68%
“…The sociodemographic and economic characteristics of the people living with HIV/Aids evidenced in this study support other background studies developed in Brazil (15,20) and around the world. (10,19,21) In the United States, depression is very common and, according to one study, (11) the overall prevalence rate was estimated at 6.6%, while ranging between 5 and 10% in PLHA. Similarly, in a Brazilian study, a higher prevalence rate of depressive symptoms was found in PLHA, equivalent to 27.6%, measured by the BDI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations